Site Characterization Using Masw and Mapping of Average Shear Wave Velocity for Jammu, Jammu and Kashmir (International Journal of Innovative Research in Engineering & Management, 2022)
Jammu is a fast-growing and major city in  northern India, in UT Jammu & Kashmir. Jammu, the  winter capital, is a city of temples, a symbol of ancient  values, and has a distinct image due to its legacy,  geography, and connections. The present study focuses on  Site Characterization through geophysical testing i.e.,  (Active) Multi-channel Analysis of Surface Waves. Multi channel analysis of surface wave (MASW) is used for  measuring the shear wave velocity (VS) at twenty-one (21)  locations within Jammu city using TROMINO. Shear  Wave velocity profiles over 30 m depth have been  generated at each location using Grilla Software. Using the  VS30 values seismic site characterization of the locations  has been carried according to National Earthquake Hazard  Reduction Program (NEHRP) guidelines. VS30 is a  significant input for evaluating the seismic response of a  soil deposit to earthquakes because it is a dynamic property  of soils. The value of VS30 for the sites is varying from 271  m/s to 475 m/s. Site characterization revealed that most of  the sites fall under C and D categories. From the VS30  values further a map was generated using a GIS platform  that can be used for hazard estimation.
Keywords: Multi-channel Analysis of Surface Waves (MASW); Jammu (Jammu and Kashmir); Shear Wave Velocity; Seismic Site Characterization